THE EFFECT OF GIVING MEMORIZATION ASSIGNMENTS TO INCREASE READING COMPREHENSION IN CLASS X STUDENTS OF SMA N 1 TONDANO - Imanuel Prima Rotinsulu; Nihta V. F. Liando; Rinny Rorimpandey (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of this study was to investigate whether memorization assignment can increase student reading comprehension or not. This study included 30 students from class X1 at SMA N 1 Tondano. This was a quantitative study that used a pre-experimental design with a pre-test and post-test design. Data from the pre-test and post-test were collected using a matching and essay test, both of which had 18 items, with the matching test having 10 numbers and the essay test having 8 numbers. The findings of this study revealed a significant difference in achievement between the pre-test and post-test. The highest pre-test score obtained by students is 60, and the highest post-test score obtained by students is 90. It can be concluded that the effect of giving memorization assignment can increase students reading comprehension. English teacher are advised to give the students memorization assignment at SMA Negeri 1 Tondano because it can increase students reading comprehension.